In memory of Eduard Vakarin (Condensed Matter Physics, 2015)
On May 22, 2015 a sudden regrettable death took away Eduard Vakarin at an early age. Although Vakarin never held a prominent academic position, he established a reputation in the statistical mechanical theory of Condensed Matter by his investigation of different real coupled systems. The results he obtained are significant from both fundamental and practical perspectives.